THE INFLUENCE OF IMPRESSION MANAGEMENT OF SCHOOL LEADERS ON FOLLOWERS: A CASE STUDY IN A SECONDARY SCHOOL IN MAURITIUS - Congo-Poottaren, Nathalie (PEOPLE: International Journal of Social Sciences, 2017)
Impression management forms an integral part of the arena of tools which school leaders use to influence their followers. School leaders are now called upon to lead schools in the wake of challenges and changes brought about by new policies and reforms in the educational sector. They are more and more being held accountable for the performance of their schools. This has created very complex situations at school. Many school leaders have had to revisit their practice and consider how to create the appropriate opportunities at school. One solution they found was to reconsider the links established with their followers. Although, not well documented in the literature, the role of followers has been recognized as being important in the interplay between leaders and followers. This paper examines the influence of impression management of school leaders on followers. The followers are the section leaders who have, by nature of their duties, to work closely with the school leaders (n=7). A qualitative research design was followed. Semi-structured interviews with the section leaders were used to collect data while content analysis was used to identify themes and analyze the data collected. The research established that section leaders experienced many challenges and confusion when school leaders resort to using impression management. Based on the findings of this study, measures were suggested on how school leaders could have resort to more effective practices in order to influence followers.